2021
DOI: 10.1016/j.compstruct.2021.113693
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of 3D printed interpenetrating phase composites with spinodal topologies

Abstract: The mechanical response of interpenetrating phase composites (IPCs) with stochastic spinodal topologies is investigated experimentally and numerically. Model polymeric systems are fabricated by Polyjet multi-material printing, with the reinforcing phase taking the topology of a spinodal shell, and the remaining volume filled by a softer matrix. We show that spinodal shell IPCs have comparable compressive strength and stiffness to IPCs with two wellestablished periodic reinforcements, the Schwarz P triply perio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(18 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…This study will also motivate several areas of interest for future work, including acoustic isolation and impact mitigation. We envision that these bi-material enhancement on strength and energy absorption can be extended to other plate-based topologies and minimal surface-based topologies (i.e., spinodal lattices [33,41,42] or triply periodic minimal surfaces [43][44][45]) that can be realized via a wide variety of additive manufacturing methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study will also motivate several areas of interest for future work, including acoustic isolation and impact mitigation. We envision that these bi-material enhancement on strength and energy absorption can be extended to other plate-based topologies and minimal surface-based topologies (i.e., spinodal lattices [33,41,42] or triply periodic minimal surfaces [43][44][45]) that can be realized via a wide variety of additive manufacturing methods.…”
Section: Discussionmentioning
confidence: 99%
“…One way to increase the energy absorption without significantly compromising the stiffness and strength of an open-cell lattice is to introduce a much softer material into its complementary void space, resulting in a bi-material interpenetrating phase composite (IPC) [30,31]. These IPCs benefit from two topologically interconnected material phases exhibiting enhanced energy absorption by different deformation mechanisms including buckling suppression, crack resistance, or stress redistribution at the interface [32][33][34]. The enhanced energy absorption through IPC designs, however, have two main disadvantages: (i) the design approach is not suitable for closed-cell lattices where the bi-continuous interpenetrating layout cannot be achieved; (ii) it often comes at the cost of increasing mass [35], due to the introduction of additional topology from the second phase.…”
Section: Introductionmentioning
confidence: 99%
“…MiniSurf will certainly support a number of future projects in this field. As examples, MiniSurf is currently used in two ongoing projects in our research group: (i) Mechanical properties of 3D printed interpenetrating phase composites with shell-based reinforcements [44]. MiniSurf is used to generate CAD files for Schwarz P surface shell-based reinforcements for interpenetrating phase composites.…”
Section: Impact Overviewmentioning
confidence: 99%
“…Although IPCs are natural candidates for advanced 3D designs, such as beam, shell, and plate lattices, manufacturing constraints have, so far, limited these complex reinforcement topologies to macroscopic polymer/polymer pairings (19,(21)(22)(23), with nearly no demonstration of metal/ceramic systems or at small scale. While a small number of studies have shown additively manufactured metal/ ceramic IPCs (24,25), the fabrication process limited the reinforce ment topology to simple millimeterscale woodpile designs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stress concentrations at the sharp reinforcement lattice nodes were identified to promote early failure. In polymeric IPCs, triply periodic minimal surface (TPMS) reinforcements (21)(22)(23)26) demonstrated increased stiffness, strength, and toughness over periodic beam based architectures and stochastic nonminimal surface reinforce ments. TPMS topologies, such as gyroid surfaces, are smoothly interconnected 3D shells with zero mean curvature and negative Gaussian curvature at any given point.…”
Section: Introductionmentioning
confidence: 99%